A Computational Fluid Dynamics Study of Turbulence, Radiation, and Combustion Models for Natural Gas Combustion Burner - Yik Siang Pang; Woon Phui Law; Kang Qin Pung; Jolius Gimbun (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
This paper presents a Computational Fluid Dynamics (CFD) study of a natural gas combustion burner focusing on the effect of combustion, thermal radiation and turbulence models on the temperature and chemical species concentration fields. The combustion was modelled using the finite rate/eddy dissipation (FR/EDM) and partially premixed flame models. Detailed chemistry kinetics CHEMKIN GRI-MECH 3.0 consisting of 325 reactions was employed to model the methane combustion. Discrete ordinates (DO) and spherical harmonics (P1) model were employed to predict the thermal radiation. The gas absorption coefficient dependence on the wavelength is resolved by the weighted-sum-of-gray-gases model (WSGGM). Turbulence flow was simulated using Reynolds-averaged Navier-Stokes (RANS) based models. The findings showed that a combination of partially premixed flame, P1 and standard k-ε (SKE) gave the most accurate prediction with an average deviation of around 7.8% of combustion temperature and 15.5% for reactant composition (methane and oxygen). The results show the multi-step chemistry in the partially premixed model is more accurate than the two-step FR/EDM. Meanwhile, inclusion of thermal radiation has a minor effect on the heat transfer and species concentration. SKE turbulence model yielded better prediction compared to the realizable k-ε (RKE) and renormalized k-ε (RNG). The CFD simulation presented in this work may serve as a useful tool to evaluate a performance of a natural gas combustor.